Teachers’ beliefs on scientific models and the role of mathematisation - Østergaard, Maria Kirstine; Jankvist, Uffe Thomas; Misfeldt, Morten; Pedersen, Mathilde Kjær (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The definition and application of models and modelling differ significantly in the different STEM subjects. This may lead to learning-related challenges for the students, especially in upper secondary school. One perspective that might shed a light on the differences and similarities between the subjects’ models and modelling processes is the role of mathematics in them as well as the nature of a possible mathematisation. In an educational context, the teachers’ perception of this matter is central. In this paper, we investigate how two upper secondary school science teachers characterise models in their respective subjects, biology and chemistry. By comparing the teachers’ statements from an interview partly to existing literature and partly to statements from an expert informant, we analyse their beliefs about the role of mathematics and mathematisation within these models, leading to a discussion of not only the differences in the concept of model, but also of how teachers’ beliefs may influence the students’ understanding of models and modelling in the two scientific subjects.